2016
DOI: 10.1042/bst20150247
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specificity using chimeric antigen receptors: the future of regulatory T-cell therapy?

Abstract: Adoptive regulatory T-cell (Treg) therapy using autologous Tregs expandedex vivois a promising therapeutic approach which is currently being investigated clinically as a means of treating various autoimmune diseases and transplant rejection. Despite this, early results have highlighted the need for potent Tregs to yield a substantial clinical advantage. One way to achieve this is to create antigen-specific Tregs which have been shown in pre-clinical animal models to have an increased potency at suppressing und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 49 publications
(81 reference statements)
0
25
0
1
Order By: Relevance
“…89 Genetic modification of polyclonal Tregs with CAR to promote antigen-specificity has demonstrated that CAR Tregs mediate enhanced suppression of inflammation compared with polyclonal Tregs in mouse models of TNP-induced colitis, 96 experimental autoimmune encephalitis, 97 anti-factor VIII autoantibody formation, 98 and skin graft rejection. 99 CARs may also redirect the function of human natural Tregs. 100 HLA-A2-specific CAR Treg were recently shown to inhibit xenogeneic GVHD mediated by HLA-A2 1 peripheral blood mononuclear cells in immunedeficient mice infused with Treg:HLA-A2 1 peripheral blood mononuclear cell ratios of 1:1 to 1:2.…”
Section: Car Tregsmentioning
confidence: 98%
“…89 Genetic modification of polyclonal Tregs with CAR to promote antigen-specificity has demonstrated that CAR Tregs mediate enhanced suppression of inflammation compared with polyclonal Tregs in mouse models of TNP-induced colitis, 96 experimental autoimmune encephalitis, 97 anti-factor VIII autoantibody formation, 98 and skin graft rejection. 99 CARs may also redirect the function of human natural Tregs. 100 HLA-A2-specific CAR Treg were recently shown to inhibit xenogeneic GVHD mediated by HLA-A2 1 peripheral blood mononuclear cells in immunedeficient mice infused with Treg:HLA-A2 1 peripheral blood mononuclear cell ratios of 1:1 to 1:2.…”
Section: Car Tregsmentioning
confidence: 98%
“…Regulatory T cells (Tregs) also play a critical role in regulating the immune system by inhibiting the function of immune cells to keep immunologic self-tolerance and immune homeostasis, and an AID will occur when the specific transcription factor Forkhead box protein P3 (Foxp3) of Tregs is mutated or the CD4+CD25+ T cells are eliminated [50]. Therefore, applying Treg therapy in AIDs after being engineered to CAR-Tregs having antigen specificity may be a new choice [16,21,51,52]. CAR-Tregs can induce antigen-specific cytolysis of the targeted cell in a granzyme B-dependent way, suppressing antigen-specific effector T cells' (Teffs) response, and releasing immunosuppressive cytokines, like transforming growth factor β1 (TGF-β1) and IL-10 [53].…”
Section: Car-t Cell-derived Immunotherapy In Aidsmentioning
confidence: 99%
“…204 In addition to expansion by donor cell stimulation, alloantigen-specific Treg can also be generated through transfection of viral vectors encoding chimeric antigen receptors (CARs). 205 CARs are synthetic fusion proteins consisting of a single-chain variable fragment (scFv, a binding moiety of monoclonal antibody), an extracellular hinge, a transmembrane region, and an intracellular signaling domain. Transfected CARs in nTregs are capable of redirecting the specificity of nTregs toward the desired antigens without altering their regulatory phenotype or epigenetic stability.…”
Section: Regulatory Immune Cell Infusionsmentioning
confidence: 99%